Presentazione del “Manifesto del Terzo Paesaggio” di Gilles Clément, giovedì 12 Ottobre, Triennale Lab, Milano - Chiara Lanzoni (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
“Manifeste du Tiers paysage” is the first book translated in Italian of the French landscaper Gilles Clèment, work that becomes part of his continuous research on the edge of the equilibrium between planning experience and theoretical treatment. Through the expression “Tiers paysage”, unsettled fragment of the planetary garden, Clèment indicates all the places in which man leaves to the only nature the landscape evolution, where all human activities are suspended. The presentation of the work was attended by Stefano Boeri, Pierluigi Nicolin and Filippo De Pieri, the volume trustee, and was accompanied by the underlining, from the author’s part, of some key concepts: the diversity contained in these places, refugee for species that can’t find space elsewhere, the astonishment by which we have to see and to refer to nature. These concepts sustain the theme that accompanies every chapter of the book, delicately but intensely at the same time: the man consciousness of his being part of nature. And after having done this “manifest”, man can’t help feeling responsible.